Helminths in the common opossum Didelphis marsupialis (Didelphimorphia: Didelphidae), with a checklist of helminths parasitizing marsupials from Peru - Jhon D. Chero; Gloria Sáez; Carlos Mendoza-Vidaurre; José Iannacone; Celso L. Cruces (Revista Mexicana de Biodiversidad)
Between May and November 2015, 8 specimens of Didelphis marsupialis Linnaeus, 1758 (Didelphimorphia: Didelphidae) collected in San Martín, Peru were examined for the presence of helminths. A total of 582 helminths representing 11 taxa were identified (2 digeneans and 9 nematodes). Five new host records and 4 species of nematodes [Gongylonemoides marsupialis (Vaz & Pereira, 1934) Freitas & Lent, 1937, Trichuris didelphis Babero, 1960, Viannaia hamata Travassos, 1914 and Viannaia viannaia Travassos, 1914] are added to the composition of the helminth fauna of the marsupials in this country. Further, a checklist of all available published accounts of helminth parasites reported from Peru is provided. To date, a total of 38 helminth parasites have been recorded. Digeneans have the highest species richness in number and percentage (n = 19, 50%), followed by nematodes (n = 17, 45%) and acanthocephalans (n = 2, 5%). The parasites with the highest number of records were the digeneans Plagiorchis didelphidis (Parona, 1896) Stossich, 1904 (n = 4) and Rhopalias coronatus Kifune & Uyema, 1982 (n = 4) and the nematode Aspidodera sp. (n = 4). Additional sampling in this country will probably increase the richness of the helminthological inventory of this group of mammals.